Endometriosis Symptoms and Their Impacts on the Daily Lives of US Women: Results from an Interview Study - Hunsche E; Gauthier M; Witherspoon B; Rakov V; Agarwal SK (Dove Medical Press, 2023)
Elke Hunsche,1 Martha Gauthier,2 Brooke Witherspoon,2 Viatcheslav Rakov,1 Sanjay K Agarwal3 1Myovant Sciences GmbH, Basel, Switzerland; 2Endpoint Outcomes, A Lumanity Company, Boston, MA, USA; 3Center for Endometriosis Research and Treatment, University of California San Diego, La Jolla, CA, USACorrespondence: Elke Hunsche, Global Market Access and Health Economics / Outcomes Research, Myovant Sciences GmbH, Aeschengraben 27, Basel, 4051, Switzerland, Email elke.hunsche@myovant.comObjective: This interview study sought to capture patients' experiences and perceptions of endometriosis symptoms and their impacts on daily life, as described by women in their own words. Using open-ended questions and a concept-elicitation approach, this study assessed the signs and symptoms of endometriosis and their impacts on different aspects of quality of life, including daily activities, functioning, and well-being.Materials and Methods: This interview study included US women with moderate-to-severe endometriosis-associated pain who completed one of two Phase 3, randomized, double-blind, placebo-controlled trials (SPIRIT 1 or SPIRIT 2; ClinicalTrials.gov identifiers: NCT03204318, NCT03204331). Interviews were conducted via a web/Internet-based video platform or telephone by trained interviewers, using open-ended questions in a concept-elicitation approach, and probes as needed to obtain additional feedback on the burden of endometriosis. Qualitative data from the interviews were analyzed, and emerging concepts were coded by independent coders. Concept saturation was evaluated to determine if all endometriosis-related symptoms and impacts had been described by the sample of women interviewed.Results: Forty women participated in this study. In total, 18 unique symptoms of endometriosis emerged from the interviews; pelvic pain (92.5%), dyspareunia (80.0%), and heavy bleeding (75.0%) were the most commonly reported endometriosis symptoms. A total of 33 unique impacts of endometriosis symptoms were identified across 11 concepts: physical impacts, impacts on activities of daily living, social impacts, sleep impacts, emotional impacts, appearance impacts, financial impacts, sex-related impacts, work/school-related impacts, fertility impacts, and cognitive impacts. Concept saturation was achieved for both symptoms and impacts of endometriosis.Conclusion: This interview study provides substantive qualitative data on the burden of endometriosis, from the perspective of affected women in the US. The findings demonstrate the debilitating effect of endometriosis symptoms, which limit and adversely impact women's daily lives.Keywords: endometriosis, interview, concept-elicitation, gynecology, patient perspective, pain